Isolation of quinic acid from dropped Citrus reticulata Blanco fruits: its derivatization, antibacterial potential, docking studies, and ADMET profiling - Heena,; Kaushal, Sonia; Kaur, Vishaldeep; Panwar, Harsh; Sharma, Purshotam; Jangra, Raman (Frontiers in Chemistry, 2024)
Citrus reticulata Blanco sets a large number of flowers (nearly 300 flowers at the age of 3 or 4) but only 0.5 to 2% of them reach maturity and the rest of them undergo natural fruit drop since maturity. These dropped fruits are generally discarded as waste causing environmental pollution and enormous losses to farmers. In the present study, quinic acid (1,3,4,5tetrahydroxycyclohexane-1-carboxylic acid) has been isolated from the ethyl acetate fraction of methanol extract of citrus fruits dropped in April by column chromatography. Quinic acid is a ubiquitous plant metabolite found in various plants and microorganisms. It is an important precursor in the biosynthesis of aromatic natural compounds. It was further derivatized into 3,4-O-isopropylidenequinic acid 1,5-lactone (QA 1 ), 1,3,4,5-tetraacetoxycyclohexylaceticanhydride (QA 2 ) and cyclohexane-1,2,3,5-tetraone (QA 3 ). All these compounds were further tested for their antibacterial potential against foodborne pathogens i.e., Staphylococcus aureus, Bacillus spp., Yersinia enterocolitica, Escherichia coli in which QA 1 exhibited maximum antibacterial potential (MIC; 80-120 μg/mL). QA 1 revealed synergistic behavior with streptomycin against all the tested bacterial strains having FICI ranging from 0.29-0.37. It also caused a significant increase in cell constituents release in all the tested bacteria as compared to the control along with prominent biofilm reduction. The results obtained were further checked with computational studies that revealed the best docking score of QA 1 (-6.30,-5.8 and -4.70 kcal/mol) against βlactamase, DNA gyrase and transpeptidase respectively. The ADMET analysis revealed drug like properties of QA 1 having an ideal toxicity profile making it a suitable candidate for the development of antimicrobial drugs.